Chemical Properties of Inceptisol and Rice Yields Applied with Mixed Source Fertilizer (MSF) - Jauhari Syamsiyah; Sumarno Sumarno; Suryono Suryono; Winda Sari; Muhammad Anwar (UNIVERSITY OF LAMPUNG, 2018)
One effort that can be done to improve soil fertility and crop yields is fertilization. Fertilization using a mixed source fertilizer (MSF) is an option to overcome the impact of inorganic fertilizer use and organic fertilizer drawbacks. This study aims to evaluate the effects of MSF application on the chemical properties of Inceptisol and rice yields. A field experiment was conducted using a completely randomized block design (RCBD) with two factors and three replications. The first factor was the three formulas of MSF (F1, F2, F3) and the second factor was MSF doses (0, 2.5, 5, 7.5, 10 Mg ha-1). The results show that there is no significant difference on the total soil N, available soil P, plant height and total number of tillers of rice plants applied with the three MSF formulas. The increased MSF doses applied significantly improve the soil chemical properties of Inceptisol and rice yields. The application of 10 Mg ha-1 MSF increases total- N (57.89%), available-P (29.13%), exchangeable-Ca and -Mg (117% and 250%, respectively), plant height (40%) and total number of tillers (43.2%) in comparison to those without MSF application. There are interaction effects between formulas and doses of MSF on the amount of exchangeable-K, organic-C content, and CEC of the soil and rice yields. The application of 10 Mg ha-1 MSF F3 results in better effects on the amount of exchangeable-K, organic-C content and CEC of the soil, and number of productive tillers and rice yields than the application of other MSF formulas. The MSF can be used as an alternatif fertilizer that can improve Inceptisol productivity.